Corporate social performance: An analysis of corporate social responsibility implementation in the electrical energy industry - Budi Setiawan; Basuki Agus Suparno; Subhan Afifi (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2021)
Corporate Social Responsibility (CSR) is a corporate concern for the economy, society, and environment. CSR activities reflect the company's social performance (CSP), using productivity, profits, employee welfare, and product quality measurement. This research is a case study of implementing a CSR program with a CSP approach at PT. Pembangkitan Jawa Bali (PJB). It aims to describe and analyze the implementation of PJB's CSR to assess its social performance. Theoretically, this research used the concept of Corporate Social Performance, which explained the principles of corporate social responsibility, and corporate social behavior. This study used a qualitative descriptive method with in-depth interviews to analyze data collection documents. The study results showed that the implementation of PJB's social responsibility programs was focused on Community Involvement and Development (CID) by implementing four main pillars of the program, namely: PJB Smart Innovation, PJB Green Innovation, PJB Superior, and PJB Cares. CSR programs were implemented based on the company's social mapping, including four circular areas related to the community's needs. Overall, the implementation of CSR based on the Corporate Social Performance model at PT PJB positively impacted society socially, economically, and environmentally. At the same time, it also positively impacted the company by increasing its business performance.